Analysis of terms in the sasak nyunat tradition and their pedagogical implications - Ahmad Supriadi Guna Putra; Mahsun Mahsun; Burhanuddin Burhanuddin; Aswandikari Aswandikari; Saharudin Saharudin (Satwika : Kajian Ilmu Budaya dan Perubahan Sosial, 2025)
This study examines the linguistic forms and cultural meanings embedded in the nyunat (circumcision) tradition of the Sasak community from the perspective of anthropological linguistics. It addresses a research gap in which circumcision traditions in Indonesia have mostly been explored from anthropological and health perspectives. The study aims to document, classify, and interpret ritual lexicons as cultural markers that embody identity, social roles, and spiritual values. Through qualitative methods involving observation, interviews, and document analysis, supported by audio–video recordings, the research constructs a taxonomy of ritual lexicons categorized into three semantic domains—berjap ‘getting ready’, begawe ‘holding a celebration’, and perebaq jengkis ‘ending the ceremony’. This taxonomy demonstrates how ritual language organizes cultural knowledge and encodes social order. Theoretically, the study advances the field of anthropological linguistics by showing how ritual lexicons function as systems that preserve and negotiate cultural meaning across generations. Pedagogically, the findings highlight the potential integration of local ritual lexicons into heritage-based education, cultural literacy, and digital storytelling programs to promote linguistic awareness and cultural sustainability.   Penelitian ini mengkaji bentuk-bentuk linguistik dan makna budaya yang tertanam dalam tradisi nyunat (khitan) masyarakat Sasak dari perspektif linguistik antropologi. Kajian ini menanggapi kesenjangan penelitian, di mana tradisi khitan di Indonesia sebagian besar telah diteliti dari sudut pandang antropologis dan kesehatan. Penelitian ini bertujuan untuk mendokumentasikan, mengklasifikasikan, dan menafsirkan leksikon-leksikon ritual sebagai penanda budaya yang merepresentasikan identitas, peran sosial, dan nilai-nilai spiritual. Melalui metode kualitatif yang melibatkan observasi, wawancara, dan analisis dokumen yang didukung oleh rekaman audio–video, penelitian ini membangun taksonomi leksikon ritual yang dikategorikan ke dalam tiga domain semantik, yaitu berjap (‘bersiap’), begawe (‘mengadakan perayaan’), dan perebaq jengkis (‘menutup upacara’). Taksonomi ini menunjukkan bagaimana bahasa ritual mengorganisasi pengetahuan budaya dan mengodekan tatanan sosial. Secara teoretis, penelitian ini memperluas bidang linguistik antropologi dengan menunjukkan bagaimana leksikon ritual berfungsi sebagai sistem yang mempertahankan dan menegosiasikan makna budaya lintas generasi. Secara pedagogis, temuan penelitian ini menyoroti potensi integrasi leksikon ritual lokal ke dalam pendidikan berbasis warisan budaya, literasi budaya, dan program penceritaan digital untuk meningkatkan kesadaran linguistik dan keberlanjutan budaya.